Wolbachia strains in cryptic species of the Anastrepha fraterculus complex (Diptera, Tephritidae) along the Neotropical Region - Prezotto, Leandro F.; Perondini, André L.P.; Hernández-Ortiz, Vicente; Marino, Celso L. [UNESP]; Selivon, Denise (Elsevier, 2017)
Infection by Wolbachia was described previously in eleven species of Anastrepha fruit flies some of which are important pests of fruticulture. One such species is the nominal Anastrepha fraterculus, the South American fruit fly, which actually comprises a complex of cryptic species. The suggestions of using Wolbachia for the control of these pest species, make imperative a more precise characterization of the existing strains of the bacteria. In this study, population samples of the A. fraterculus complex from Brazil, Argentina, Peru, Ecuador, Colombia, Guatemala and Mexico were analyzed for Wolbachia infection. The bacteria were genotyped by the MLST and WSP Typing methodologies. All samples were infected with Wolbachia of supergroup “A”. For each of the five MLST genes, unique as well as already known alleles were detected. Nineteen sequence types for the concatenated sequences of the five MLST genes, and twenty wsp alleles were found in the samples. Host-specific haplotypes, shared strains among distinct hosts, and more than one strain of Wolbachia were found in some population samples. Recombination among the MLST genes and intragenic recombination between wsp haplotypes was rare. Phylogenetic analysis showed a great similarity among the Wolbachia strains in the A. fraterculus complex. However, some strains of Wolbachia are found throughout the Neotropical Region and there are specific strains in determined geographical areas.
Keywords: Bacteria; Fruit flies; MLST; Phylogeny; Recombination; WSP Typing